New Trends in Humanitarian Assistance – The Private Turn in Humanitarian Aid - Montesclaros, Jose (2018)
To bridge funding gaps in humanitarian assistance, states will need to re-examine their roles, relative to the private sector. Humanitarian technologies offer a potential high-volume, low-profit margin sector which can be an entry point for private companies.